Knowledge and practice regarding retinopathy of prematurity among paediatricians - Shrestha, Priyanka; Mathema, Smriti; Pradhan, Pranil Man Singh (Journal of Kathmandu Medical College, 2022)
Background: Retinopathy of prematurity, a vision threatening disease of the preterm occurs due to abnormal retinal vasculature development. Early detection and timely management, prevents blindness. Paediatricians, the primary care providers, require good knowledge of risk factors, time for screening, and referral to an ophthalmologist for their management.Objectives: To study knowledge and referral practices for retinopathy of prematurity followed by registered paediatricians in Nepal.Methods: This study was a questionnaire-based descriptive cross-sectional study among 81 paediatricians of Nepal from October 2021 to December 2021. A self-administered questionnaire was sent to all registered paediatricians in Nepal via Google Forms. The paediatricians who did not respond were excluded from the study. Descriptive statistics, frequency tables, and percentages were calculated using SPSS. Ethical clearance was obtained from Institutional Review Committee of Kathmandu Medical College.Results: Eighty-one paediatricians participated in the study. All of them were aware of retinopathy of prematurity. Eighty (98.8%) were aware that low gestational age was an important risk factor. Only 23 (28.4%) of the paediatricians stated that the first screening should be done within 30 days of life. Eighty (98.8%) paediatricians responded that retinopathy of prematurity is treatable. Lack of well-equipped transportation system for sick babies to eye centres was the major barrier reported.Conclusion: Awareness regarding risk factors, screening, and referral protocols for retinopathy of prematurity among paediatricians is needed. Multidisciplinary team, formulation and implementation of guidelines to prevent blindness secondary to retinopathy of prematurity is important.